Impact of the Constructivist EDGA Model on Learning Some Basic Volleyball Skills for Middle School Female Students - Hussein, Amena Kareem (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This research aimed to identify the effect of using the constructivist EDGA model on developing female students’ performance of some basic volleyball skills. Material and methods. The researcher used the experimental method with an equivalent group design with a pre-test and post-test to suit the nature of the research problem. The researcher then identified the research population as the fourth-grade middle school students at the March 11 Girls’ Middle School in the Kirkuk Education Directorate, who numbered (151) students. The researcher used the statistical package to reach scientific results on which she based her research conclusions. Results. The study found significant differences in basic volleyball skills (underhand serve, overhand pass, and underhand pass) in favour of the experimental with the arithmetic mean for basic volleyball skills (36.700, 28.950, 25.350), respectively. However, the control group obtained the arithmetic mean (26.050, 20.850, 18.150), respectively. The constructivist EDGA model was used in the curriculum, stimulating students' minds and helping them develop. The development unit's clear goals, aligned with the student's current level, will enhance learning and help achieve the educational objectives. Conclusions. One of the most important of these is using the educational curriculum according to the constructivist EDGA model, which has achieved remarkable development in basic volleyball skills. Using the stages and steps of the EDGA model, along with the nature of the skills and the sample level, led to the theoretical and practical learning of research skills. The research recommendations came as follows: Emphasizing the adoption of the EDGA model in educational curricula related to learning sports skills. Urging the use of modern methods and models in learning basic volleyball skills.